λ ∼ 4.7 μm Quantum Cascade Distributed-Feedback Lasers for Free-Space Communications - Morgan Turville-Heitz; Robert Marsland; Jae Ha Ryu; Steven A. Jacobs; Jeremy D. Kirch; Tom Earles; Steven Ruder; Kevin Oresick; Benjamin Knipfer; Dan Botez; Luke J. Mawst (Photonics)
Quantum cascade lasers (QCLs) have emerged as promising candidate sources for free-space communications. High optical power densities, short photon lifetimes, and low internal capacitance are important factors influencing the transmission bandwidth. We report the design and fabrication of 4.7 <semantics>μ</semantics>m emitting, 1.5 mm cavity length, single-mode distributed-feedback QCLs, with a CW front-facet output power of 165 mW and a calculated photon lifetime of 11.6 ps, resulting in an electrically limited CW modulation with a 3 dB cutoff at 850 MHz.